The Effectiveness of Kneading Massage in Reducing Dysmenorrhea Pain in Stikes Aksari Indramayu Students - Masliha Masliha (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Menstruation is a bleeding process that occurs periodically or cyclically from the endometrium. During menstruation, complaints and disorders often occur, especially in productive women, especially teenagers, who often experience menstrual pain or dysmenorrhea. One of the nursing actions to overcome this is kneading massage. The aim of the research was to determine the effectiveness of kneading massage in reducing dysmenorrhea pain in Stikes Aksari Indramayu students. This type of research is quantitative, using a quasi-experimental method with a one-group pretest-posttest design approach. The characteristic of this type of research is that it reveals cause-and-effect relationships by involving a group of subjects. The subject group was observed before the intervention, then observed again after the intervention. The population in this study was all female students at the Aksari College of Health Sciences (STIKes), totaling 46 people in April 2024. The sampling technique used was accidental sampling. The data collection technique uses primary data directly obtained from respondents, with a sample size of 28 people. Data analysis uses frequency distribution and paired samples test statistical tests. Results: most of the respondents, 17 people (60.7%), had menarche at the age of 11 years; all respondents, 28 people (100%), had high school education; most of the respondents, 12 people (42.9%), had a family history of experiencing pain during menstruation; and the majority of respondents, 19 people (67.9%), had experienced experiencing severe pain during dysmenorrhea. The results of calculating the